Detection of hydrogen fluoride (HF) gas by Mg12O11-X (X = S, P, N, and B) nanosurfaces - Stephen A. Adalikwu; Hitler Louis; Henry O. Edet; Innocent Benjamin; ThankGod C. Egemonye; Ededet A. Eno; Adedapo S. Adeyinka (Chemical Physics Impact, 2022)
In this paper, using the density functional theory (DFT) at the B3LYP/6-311++G (d, p) level of theory, the effectiveness and abilities of Mg12O12 doped with B, N, P and S as adsorbents: Mg12O11S, Mg12O11N, Mg12O11P, and Mg12O11B for HF gas was investigated using the frontier molecular orbital, natural bond orbital, density of state, adsorption energy and topology analysis. From our results for adsorption energies, all calculated Eads for various modifications are negative which is an indication of the surfaces potential to adsorbed HF gas molecule. Nonetheless, the highest Eads was observed at HF-Mg12O11S with -42.06 kJ/mol while the lowest was observed at HF-Mg12O12 with Eads of -8.78 kJ/mol. The total density of state (DOS) analysis also shows that, the doping of heteroatoms on Mg12O12 surface decreases the HOMO, LUMO band gap, and therefore, has a significant influence on the electronic properties of the surfaces. Also, Mg12O11S was observed with the highest adsorption energy of -42.06 kj/mol compared to other surfaces. The Mg12O11S adsorption potentials are supported by other findings. Therefore, Mg12O11S shows considerably more potential than others for the adsorption of HF molecule.